Differences in knowledge and attitudes between adolescents about HIV/AIDS, and their implications for targeted interventions - Purwanto, Edi; Gumilang, Lingga Arta (Institute of Computer Science (IOCS), 2025)
This study analyzed the differences in levels of knowledge and attitudes towards HIV/AIDS between adolescent boys and girls and encouraged them towards more targeted interventions. Using a quantitative approach, data was collected through a survey of 300 respondents aged 15–19 years in urban and rural areas. The results show that adolescent girls tend to have a higher level of knowledge about HIV/AIDS transmission and prevention compared to adolescent boys. However, positive attitudes towards people with HIV/AIDS are higher in adolescent boys. Factors such as access to information, parental education, and peer influence play a significant role in shaping knowledge and attitudes. Based on these findings, the intended intervention needs to consider gender differences to improve the effectiveness of HIV/AIDS prevention programs. Programs for adolescent boys can be focused on improving basic knowledge, while programs for adolescent girls require the stress of the importance of empathy and stigma reduction.